Detection of Highly Differentiated Genomic Regions Between Lotus (Nelumbo nucifera Gaertn.) With Contrasting Plant Architecture and Their Functional Relevance to Plant Architecture - Zhao, Mei; Yang, Ju-Xiang; Mao, Tian-Yu; Zhu, Huan-Huan; Xiang, Lin; Zhang, Jie; Chen, Long-Qing (Frontiers in Plant Science, 2018)
The lotus (Nelumbo nucifera Gaertn.) is one of the most economically and ornamentally important perennial aquatic plants. Plant architecture is an important trait for lotus classification, cultivation, breeding, and applications. In this study, traits representing plant architecture were measured in 390 lotus germplasms for 3 years. According to the phenotypic distribution, 21 large architecture (LA) and 22 small architecture (SA) germplasms exhibiting extreme phenotypes were selected as representatives of plant architecture. Microscopy analyses revealed that LA lotuses possessed far more vertical cells and longer cell lengths than SA lotuses, and there was a closer linear relationship between vertical cell number and plant architecture than cell length and plant architecture. Furthermore, based on whole genome re-sequencing data from 10 LA and 10 SA lotus germplasms, fixation index (FST) genome scan identified 11.02 Mb of genomic regions that were highly differentiated between the LA and SA lotus groups. Chi-square test revealed that 17,154 single nucleotide polymorphisms (SNPs) and 1,554 insertions and‎ deletions (InDels) showed distinct allelic distribution between the LA and SA lotus groups within these regions. A total of 126 variants with distinct allelic distribution in the highly differentiated region were predicted to cause amino acid changes in 60 genes. Among the 41 genes with functional annotation, the expression patterns of six genes involved in cell division and cell wall construction were confirmed using quantitative reverse transcription PCR (qRT-PCR). In addition, 34 plant architecture-associated InDel markers were developed and verified in the remaining 11 LA and 12 SA lotus plant architecture representatives. This study identified promising functional markers and candidates for molecular breeding and will facilitate further elucidation of the genetic mechanisms underlying plant architecture in the lotus.